Everyday Sectarianism in Urban Lebanon - Muneeza Rizvi (International Institute of Islamic Thought, 2018)
In Everyday Sectarianism, anthropologist and filmmaker Joanne Nucho examines the inextricable links between sectarian belonging, Lebanon’s confessional system of governance, and neighborhood infrastructures developed in the absence of the state (a refrain throughout the book is wayn al dawleh?). Departing from orientalist accounts that represent sectarianism as a static and primordial conflict of identities, Nucho argues that sectarianism in Lebanon is a modern, relational, and political process of continual (re)construction. In this sense, her account draws from existing literature on the Lebanese state that emphasizes sectarianism’s contingent character (see, for example, Ussama Makdisi 2000; Max Weiss 2010; Suad Joseph 2008). For these scholars, sectarianism is not a given mode of being in the world. Rather, it is a project inseparable from questions of gender, class, geography, and the state, and cannot be “collapsed onto religion or theology” (4).